Penerapan Terapi Meditasi Mindfulness Islami untuk Mengurangi Tingkat Kecemasan pada Ibu Hamil Trimester III di Puskesmas Purbaratu Tasikmalaya - Dina Novita Utami; Dudi Hartono; Peni Cahyati (NAJ Nursing Applied Journal, 2025)
Anxiety often arises during pregnancy due to both physical and psychological changes that can negatively impact the health of both the mother and the fetus. These changes may include hormonal fluctuations, fear of labor, and concerns about the baby’s wellbeing. In Indonesia, approximately 28.7% of 373,000 pregnant women in their third trimester experience anxiety as they approach labor. If left untreated, anxiety during pregnancy can lead to complications such as prolonged labor, low birth weight, and postpartum depression. Therefore, early and appropriate intervention is crucial. This study aims to describe the application of Islamic mindfulness meditation therapy as a non-pharmacological intervention to reduce anxiety in pregnant women at Puskesmas Purbaratu, Tasikmalaya. Anxiety is a condition in which an individual feels uneasy, worried, or uncomfortable. Islamic mindfulness meditation therapy is a relaxation technique that integrates spiritual practices with mental focus through meditation, allowing the soul and mind to be calm, centered, and connected with God. It includes dhikr (remembrance of Allah), controlled breathing, and contemplation of positive thoughts. The method used in this study is a case study involving two primigravida pregnant clients experiencing moderate anxiety. Data were collected through interviews, observations, and measurements using the Hamilton Anxiety Rating Scale (HARS). The results indicate that Islamic mindfulness meditation therapy significantly reduced anxiety levels from moderate to mild after five consecutive days of implementation. This was achieved through a combination of breathing exercises, spiritual reflection, and relaxation. This study concludes that Islamic mindfulness meditation can be an effective, affordable, and spiritually enriching alternative therapy to reduce anxiety in pregnant women, especially during the vulnerable third trimester. It is recommended that health workers consider incorporating this method into antenatal care programs.